Antarctic ice growth before and after the Eocene‐Oligocene transition: New estimates from clumped isotope paleothermometry. (26th October 2015) - Petersen, S. V.; Schrag, D. P.
Abstract: Across the Eocene‐Oligocene transition, the oxygen isotopic composition (δ 18 O) of benthic and planktonic foraminifera increased by over 1‰. This shift is thought to represent a combination of global cooling and the growth of a large ice sheet on the Antarctic continent. To determine the contribution of each of these factors to the total change in δ 18 O, we measured the clumped isotopic composition of planktonic foraminifera tests from Ocean Drilling Program Site 689 in the Southern Ocean. Near‐surface temperatures were 12°C in the intervals 0–1.5 Myr before and 1–2 Myr after the major (Oi‐1) transition, in agreement with estimates made using other proxies at nearby sites. Temperatures cooled by 0.4 ± 1.1°C between these intervals, indicating that the long‐term change in δ 18 O seen in planktonic foraminifera at this site is predominantly due to changes in ice volume. A larger instantaneous cooling may have occurred during Oi‐1 but is not captured in this study due to sampling resolution. The corresponding change in the isotopic composition of seawater (δ 18 Osw ) is 0.75 ± 0.23‰, which is within the range of previous estimates, and represents global ice growth equivalent to roughly 110–120% of the volume of the modern Antarctic ice sheet or 80–90 m of eustatic sea level change. Key Points: Clumped isotope proxy applied to Eocene/Oligocene foraminifera Majority of oxygen isotopes change at EOT due to ice volume, not cooling